2022
DOI: 10.3389/fendo.2022.994406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity status on adolescent bone mineral density and saturation effect: A cross-sectional study

Abstract: BackgroundThe effect of obesity status on bone mineral density (BMD) in adolescents and whether there is a saturation effect is still insufficient. A cross-sectional study of adolescents aged 12–19 was conducted to investigate them.MethodsWeighted multivariate linear regression models were used to assess the relationship between obesity status and BMD via datasets from the National Health and Nutrition Examination Survey 2011–2018. The nonlinear relationships and saturation values were ascertained by fitting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In addition, our results found MS components were independent risk factors for HUA prevalence, including overweight, hypertension, dyslipidemia. The positive relationship between overweight and the presence of HUA has been documented in previous study and HUA prevalence was reported to reach 66.9% in obese individuals [2,31]. The nding may be directly explained by the fact that increased amount of dietary purine intake in obese subjects.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, our results found MS components were independent risk factors for HUA prevalence, including overweight, hypertension, dyslipidemia. The positive relationship between overweight and the presence of HUA has been documented in previous study and HUA prevalence was reported to reach 66.9% in obese individuals [2,31]. The nding may be directly explained by the fact that increased amount of dietary purine intake in obese subjects.…”
Section: Discussionmentioning
confidence: 57%
“…[7][8][9][10] In previous studies, body mass index (BMI) has been proven to be closely related to BMD. [11][12][13][14][15] In a cross-sectional study of 4056 adolescents ages 12 to 19, Wang et al found that BMI was significantly associated with total BMD, which remained significant in subgroups stratified by gender, age, ethnicity, and standing height. [12] Li et al evaluated 2218 participants aged 40 to 59 years, and found that BMI was positively related with lumbar BMD in middle-aged adults.…”
Section: Relationship Between Bmi and Bmdmentioning
confidence: 99%
“…[11][12][13][14][15] In a cross-sectional study of 4056 adolescents ages 12 to 19, Wang et al found that BMI was significantly associated with total BMD, which remained significant in subgroups stratified by gender, age, ethnicity, and standing height. [12] Li et al evaluated 2218 participants aged 40 to 59 years, and found that BMI was positively related with lumbar BMD in middle-aged adults. [13] Another study based on 3296 participants aged 50 years and older confirmed a positive correlation between BMI and BMD in older adults.…”
Section: Relationship Between Bmi and Bmdmentioning
confidence: 99%
See 2 more Smart Citations